A revision of the genus Gondwanoscurus Jezek (Diptera: Psychodidae) - Curler, Gregory R. (Zootaxa, 2009)
Gondwanoscurus Jezek (Psychodidae: Psychodinae) is revised to include seven species. Gondwanoscurus cruciferus sp. nov. and G. ornithostylus sp. nov. from Thailand are described. Three described species are transferred from Telmatoscopus Eaton to Gondwanoscurus: G. ejundicus (Quate), G. eximius (Quate) and G. praecipuus (Quate). The adult male and female of G. ejundicus and G. mcclurei (Quate) and the adult male of G. eximius and G. praecipuus are redescribed. Keys to adult males of the seven known species and females of the four species for which they are known are provided, and the relationship of Gondwanoscurus to other Paramormiine genera is discussed.